2018
DOI: 10.5430/wje.v8n2p114
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Predictive Power of Academic Achievement, Learning Approaches and Self-Regulatory Learning Skills on University Entrance Exam Scores Using Path Analysis

Abstract: A good analysis of the success factors in the university entrance exam, which is an important step for academiccareers of students, is believed to help them manage this process. Properties such as self-regulation and learningapproaches adopted by students undoubtedly influence their academic achievement as well as their success inuniversity entrance exams. However, it is not exactly known how the direct and indirect relations between thesevariables are, and which variable has more effect on success. This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Other studies conducted on the Turkish university entrance examination in the Turkish context focused on the relationship between students’ school academic achievement and university entrance examination scores or students’ perceptions about the university entrance exam system. For example, Ilhan Beyaztaş and Göçer-Şahin (2018) made an investigation of the predictive power of academic achievement on Turkish university entrance exam scores and found that the most important factor affecting the success of university entrance exam was students’ cumulative grade point average in their national diploma grades. Similarly, Karatas et al (2013) examined the correlation among the high school senior students’ academic performance and Turkish university entrance exam points.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies conducted on the Turkish university entrance examination in the Turkish context focused on the relationship between students’ school academic achievement and university entrance examination scores or students’ perceptions about the university entrance exam system. For example, Ilhan Beyaztaş and Göçer-Şahin (2018) made an investigation of the predictive power of academic achievement on Turkish university entrance exam scores and found that the most important factor affecting the success of university entrance exam was students’ cumulative grade point average in their national diploma grades. Similarly, Karatas et al (2013) examined the correlation among the high school senior students’ academic performance and Turkish university entrance exam points.…”
Section: Literature Reviewmentioning
confidence: 99%